(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
The work presents and analyses the distinctive features of restoration of the natural river runoff as well as their deficiencies. It suggests a new, mathematical statistical method of restoration of the natural river runoff, which differs from the traditional method of water intake summation by its reliability and higher accuracy.